Flow cytometric phenotyping and analysis of T regulatory cells in multiple myeloma patients - Muthu Raja, K R; Kovárová, L; Stossová, J; Hájek, R (Klinicka onkologie, 2011)
Multiple myeloma (MM) is a plasma cell (PC) disorder and associated with immune impairments. Flow cytometry based phenotyping and quantification of regulatory T cells (Tregs) enable to monitor the immune status of myeloma patients. Apart from enumeration of Tregs, functional characterization using proliferation or suppression assay adds key value in demonstrating the functional value ofTregs. Our study revealed that in MM patientsTregs are elevated compared to healthy subjects, which demonstrate the immune deregulation in MM.
Keywords: Flow Cytometry; T-Lymphocytes, Regulatory; mnohočetný myelom; Immunophenotyping; regulační T-lymfocyty; průtoková cytometrie; imunofenotypizace; Humans; Multiple Myeloma; lidé